Strategies to Foster Engagement, Empathy, Equity, and Ethics in Public Service: A Conceptual Model for Public and Nonprofit Administrators. (3rd September 2022) - Sweeting, Karen D.
Abstract: Discrimination, racism, and marginalization create significant social, economic, and emotional implications for people of color, low income, Latinx, women, LGBTQIA, and people of specific national origins who frequently generate inequitable outcomes in organizational, societal, and individual experiences. The 4Es (engagement, empathy, equity, and ethics) provide a lens to deliberately and proactively guide public and nonprofit administrators, as agents of change, to avoid hostile, discriminatory, and biased negative public service experiences. This article presents eight actionable types of initiatives that integrate the 4Es to facilitate a more equitable value orientation in contemporary public administration. The eight types of initiatives are meant to foster reflective practices and guide social change through strategic action and engaged leadership aimed at eradicating disparities and biases in policies, practices, behaviors, actions, and outcomes in public service.